Comparison of apical extrusion of sodium hypochlorite in immature teeth after needle irrigation, ultrasonic irrigation, EDDY, Er:YAG, and diode lasers - GÖKER KAMALI, SELİN; TÜRKAYDIN, DİLEK (My University, 2023)
© 2022, The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature.This study aimed to assess the apical extrusion of sodium hypochlorite in immature teeth caused by needle irrigation, ultrasonic irrigation, EDDY, Er:YAG, and diode lasers. Seventy-five human maxillary anterior teeth were selected. After the apical 3 mm of the roots was resected, the canal lumen was enlarged with #2 to #5 Gates-Glidden burs. The teeth were fixed to the lid of a flat-sided clear plastic container, and the plastic containers were filled with 0.2% agarose gel containing 1 mL of 0.1% m-cresol purple. Then, the specimens were allocated into five groups according to the irrigation activation techniques: needle irrigation, ultrasonic irrigation, EDDY, Er:YAG laser, and diode laser. The apical extrusion of sodium hypochlorite caused the color change in the gel. The containers were digitally photographed, and the percentage of pixels of irrigant extrusion (the color change) in each photograph was calculated. The diode laser group showed a significantly lower percentage of pixels than needle irrigation, EDDY, and Er:YAG laser (p 0.05). All the groups caused irrigant extrusion in the immature teeth. The diode laser and ultrasonic irrigation caused less sodium hypochlorite extrusion than EDDY and Er:YAG laser. The needle irrigation showed more irrigant extrusion than the only diode laser group.
Keywords: Tıp; Dahili Tıp Bilimleri; Dermatoloji; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Dermatology; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; DERMATOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; DERMATOLOGY; Cerrahi; Surgery; Apical extrusion; Diode laser; EDDY; Er:YAG laser; Immature teeth; Ultrasonic irrigation